Tracing the phase of focused broadband laser pulses - Hoff, Dominik; Krüger, Michael; Maisenbacher, Lothar; Sayler, A. Max; Paulus, Gerhard G.; Hommelhoff, Peter (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Precise knowledge of the behavior of the phase of light in the focus of a laser beam is fundamental to understand and control laser-driven processes. More than a hundred years ago the axial phase evolution for focused monochromatic light beams was described and is now commonly known as the Gouy phase [1]. Recent theoretical work has brought into question the validity of applying this monochromatic phase formulation to the broadband laser pulses becoming ubiquitous today [2]. The need for investigation of the spatial behavior of the local carrier-envelope phase (CEP) is also underscored by experimental studies, which suggest deviations from the monochromatic Gouy phase (see for instance [3]).
CRIS-Team Scopus Importer:2019-11-15